the community's economy in covid PENDAMPINGAN DAN PELATIHAN ZAKAT DALAM MENINGKATKAN PEREKONOMIAN MASYARAKAT DI ERA PANDEMI COVID-19 DI DESA BINAAN 16 ULU PALEMBANG - RULITAWATI RULITAWATI; PURMANSYAH APRIADI; HENDRI NUR ALAM; YUNIAR HANDAYANI; HABIBUR RACHMAN (Raudhah - Proud To Be Professional, 2022)
Zakat mentoring and training activities in an effort to improve the community's economy in the era of the Covid-19 pandemic which was carried out in the fostered village of 16 Ulu sub-district, Palembang city. This assistance aims to provide knowledge and socialization about empowering zakat in improving the community's economy. The community members who were targeted in this community service activity were residents and mothers who carried out the recitation at the Al Mawardi Mosque, totaling approximately 35 people, using the lecture method with direct exposure to the audience accompanied by questions and answers. The lecture method is used to explain in detail about material or materials about zakat and the community's economy that can be used by utilizing zakat. The benefits that can be obtained by participants by participating in this activity are that they can better understand zakat, types of zakat, assets that can be zakatable, mustahiq and zakat wisdom so that it can be applied in order to improve the economy. By increasing the number of people who pay zakat, it can help the community in increasing the level of the economy and reducing the level of poverty. Keywords: Assistance, Zakat Training, Community Economy